Records Management Capacity Assessment System: An Example of the Practice of Turkish Red Crescent Society - Külcü, Özgür; Uzun Külcü, Hande (Information World, 2010)
In order to be successful in records management within the administrative systems of institutions, an analysis of the existing capacity in administrative bodies and records management applications is regarded as crucial. In this respect, an evaluation of both international and national preconditions together with an analysis of the existing conditions in records management is necessary. In this study, the mentioned analysis is carried out in order to identify the conditions and problems through Records Management Capacity Assessment System with a related software program. Being developed by the collaborative work of International Records Management Trust, and the World Bank. Empirical examination was made upon the related activities of Red Crescent Society of Turkey Directorship of Communication and Archives, and the Directorship of Human Resources. The analysis aimed at locating the capacity, problems and expectations in records management of the Society. The conclusions indicated that there are diffi culties in defi ning metadata for accessing records, in restrictions to access, evaluation and annihilation processes, and concerning the application of methods among the administrative units. Moreover founding an electronic base for communication and daily correspondence should be among the priorities.
Keywords: Records management; Capacity; Evaluation; Turkish Red Crescent Society